Analisis Penyebab Laporan Keuangan Masjid Tidak Sesuai Dengan Standar Akuntansi - Widagdo, Galuh; Suprayogi, Noven (IAIN Kudus, 2022)
This study aimed to analyze the factors that caused the Takmir of Cheng Ho Mosque and Al Irsyad Mosque in Surabaya not to apply ISAK 35 in preparing financial reports. This study uses a qualitative method with a case study approach. The study's results revealed that the factors causing the Takmir not to apply ISAK 35 to the mosque's financial reports were that the mosque Takmir did not have sufficient knowledge about ISAK 35. The mosque's financial reports were presented following the financial information needs of Takmir and donors who were not complex. The presentation of mosque financial reports based on ISAK 35 is too complicated, so the cost of presenting information is high, but the relevance (benefit) for users of mosque financial reports is low. The results of this study imply that simpler mosque financial accounting guidelines or standards are needed to balance the relevance and cost of presenting mosque financial information. There needs to be the socialization of mosque financial accounting guidelines or standards for mosque Takmir.